Game of Thrones : A Feast of Crows - Book 4 - Martin, George R. R.; Dotrice, Roy 1925- (New York : Random House Audio, 2012)
The uneasy peace that exists following the death of Robb Stark is threatened by new plots, intrigues, and alliances that once again will plunge the Seven Kingdoms into all-out war for control of the Iron Throne.
Unabridged.
Originally released in audio format by HarperCollins in 2011.
Compact discs.
Read by Roy Dotrice.
Keywords: Imaginary places -- Fiction; Imaginary wars and battles -- Fiction; Peace -- Fiction; Outlaws -- Fiction; Magic -- Fiction; Dystopias; Fantasy fiction; Audiobooks